The significance of the message of the resurrection for faith in Jesus Christ - Marxen, Willi; Wilckens, Ulrich; Delling, Gerhard; Geyer, Hans-Georg; Moule, Charles Frances Digby, 1908-; Barton, Dorothea M.; Wilson, R.A. (London, UK SCM, 1968)
Includes bibliographical references and index.
Keywords: Jesus Christ -- resurrection -- theology